The impact of drought on commercial livestock farmers in South Africa. Issue 7 (3rd October 2018) - Mare, Frikkie; Bahta, Yonas T.; Van Niekerk, Walter
ABSTRACT: This article reports on a study that aimed to assess the impact of the 2015 drought in South Africa on commercial livestock producers, with specific reference to the associated drought adoption strategies. The study was based on primary data collected from 350 commercial livestock producers from seven different provinces. The findings revealed that the effect of drought had a significant impact on average herd size, livestock feeding, and sheep flock. Commercial livestock producers did not receive any form of assistance from the government. The majority of the farmers did not have any preventive measures in place during the drought. The study recommends that the government and policymakers should introduce a mechanism to support commercial livestock farmers when drought strikes.